Analisis Yuridis Kepastian Hukum Terhadap Peralihan Hak Atas Tanah dalam Jual Beli Dibawah Tangan (Studi Putusan Nomor 535/Pdt.G/2018/PN.Smg) - Desyifa Nurhidayah; Yuniar Rahmatiar; Muhamad Abas (UNES Law Review, 2023)
The process of buying and selling land should be carried out in front of an authorized official (PPAT) in order to obtain legal certainty in the form of a Sale and Purchase Deed (AJB) as evidence of the transfer of land rights or transfer of name at the Land Office. In general, there are still many buying and selling processes that are not carried out in front of PPAT or under the hands of some people. The research method used in this research uses qualitative methods and normative juridical approach methods with secondary data as the main data based on statutory approaches and primary data as supporting data obtained in the field. In this case, the sale and purchase carried out under the hand is still valid if it is in accordance with the agreement of the parties, but to ensure legal certainty, an authentic deed made by an authorized official is needed as proof of juridically valid ownership. Legal certainty in an agreement means that the agreement made by the parties applies like a binding law. Even though it is not in accordance with the provisions of the UUPA, the legal actions that occur have met the requirements of cash, light and real. The judge in deciding the case at No.535/Pdt.G/2018/PN/Smg. Stating that the sale and purchase carried out by the parties is valid, but needs to be completed with an authentic deed if it is going to change the name of the certificate or transfer of land rights.